Esterification of Some Organic Acids With Methanol and Ethanol Using Zirconium Tungstate As a Catalyst - Aboul-Magd, A.S. (Asian Journal of Chemistry, 2010)
The catalytic esterification of formic, mono-, dichloroacetic, acetic, propionic, butyric, isobutyric, valeric and isovaleric acids with methanol/ethanol have been investigated using zirconium tungstate (H-form) as a catalyst.